Analysis of the Impact of Halal Certificate on the Performance of Micro and Small Enterprises (SMEs) with the Propensity Score Matching (PSM) Method - Akbar, Gina Rhamdina; Rohman, Ibrahim Kholilul (Journal of Strategic and Global Studies, 2023)
The government passed Undang Undang No. 33, 2014 concerning Halal Product Guarantee (UUJPH) as a mandatory halal regulation in the hope of realizing protection for Muslim consumers and to provide added value for SMEs. However, until 2019, only 1% of SMEs have been certified halal (MUI, 2021). Therefore, it is important to know the impact of halal certificates on the performance of SMEs. Researchers compared the performance of SMEs that are halal certified with SMEs that have not been halal certified using quantitative research designs with the Propensity Score Matching (PSM) method. The PSM method can balance or equalize groups of research subjects with the matching method. With this method the treatment group is paired with the non-treated group based on the observed covariates. This method is used to reduce bias in the estimation of treatment exffects on observational data due to confounding factors. Propensity Score is a conditional probability of getting a certain treatment based on the observed covariates. The results of the study stated that there was a difference in performance between MSEs that were halal-certified and SMEs that were not halal-certified, but the effect of the halal certificate was not significant on the performance of SMEs